Perancangan Sistem Informasi Akuntansi Persediaan Berbasis Microsoft Access pada Apotek Mizan Palembang - Farah Salsabila; Sukmini Hartati; Eka Jumarni Fithri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Inventory management at Apotek Mizan Palembang is currently conducted manually using stock books and administrative documents, resulting in high recording error risks, delayed stock information, difficulties in controlling minimum stock levels, and time-consuming report preparation prone to errors. This study aims to design an inventory accounting information system based on Microsoft Access to address these problems. Data collection methods include interviews, observations, and questionnaires with the owner/apothecary and internal pharmacy documents. The designed system comprises tables (product, purchase/sales transaction, detail), queries (Detail, Product, Purchase/Sales Transaction), forms (Login, Main Menu, Product, Purchase/Sales Transaction), and stock card reports. Testing shows the system can automate transaction recording, update stock in real-time, and generate reports quickly and accurately. This system improves operational efficiency, strengthens inventory control, and provides more reliable information for decision-making.